Antioxidant activity and chemical characteristics in egg albumen fermented by lactid acid bacteria - Nahariah, N.; Hikmah, H.; Yuliati, F.N. (Diponegoro University, 2020)
Research on fermentation time and the addition of milk powder to egg albumen is still limited. The purpose of this study was to determine the antioxidant activity and chemical characteristics of fermented egg albumen using different levels of full cream milk powder and different microbial fermentation times. This study used a completely randomized factorial pattern design, 4 x 5 treatments with 4 replications. Research materials include egg albumen, full cream milk powder and mixed Lactic Acid Bacteria (L. bulgaricus, L.achidopillus, and Streptococcus thermopillus). The research treatments were the addition of powdered milk in different level (%) including, 0, 2, 4 and 6. Fermentation times were 0, 12, 24, 36, and 48 h, respectively. The results showed that the addition of powdered milk in different level and fermentation time had no significant effect on the antioxidant activity. The addition of different-level powdered milk was not significant on the glucose content and total protein, but it was very significant (P<0.01) on water content. The fermentation time had a very significant effect (P<0.01) on glucose levels and total protein, but it had no significant effect on the water content of albumen fermentation. Antioxidant activity did not change during the fermentation time and the addition of different-level milk powder. The 24 h fermentation time could reduce the total protein and glucose levels of egg albumen. Adding 2% milk powder could reduce the water content of egg albumen fermentation.